MANUVER LITERASI DIGITAL: UPAYA MENANGKAL CYBER SEXUAL ADDICTION - Vini Hidayani (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2020)
Cyber sexual addiction is a new phenomenon as a negative impact of technological advances in the digital age. Its existence has a bad influence both on the perpetrators and the victims they are targeting. Previous studies have shown psychological implications to health problems for people who are addicted. Therefore, digital literacy maneuvers should continue to be encouraged, both from the school environment, family, and society. This is in line with the ministry of education and culture program through the content of digital literacy material in 2017. The aim is to make the public wise to use the internet, and be more alert, so that they do not fall into problems such as cyber sexual addiction. The Quran through the QS. Al-Mukminun [23]: 5-7 far away has revealed the incompetence